Consumption of the Soluble Dietary Fibre Complex PolyGlycopleX(®) Reduces Glycaemia and Increases Satiety of a Standard Meal Postprandially - Solah, V.; O'Mara-Wallace, B.; Meng, X.; Gahler, R.; Kerr, D.; James, Tony; Fenton, H.; Johnson, S.; Wood, S. (MDPI Publishing, 2016)
The effect of consumption of PolyGlycopleX(®) (PGX(®)) was compared to wheat dextrin (WD) in combination with a standard meal, on postprandial satiety and glycaemia in a double-blind, randomised crossover trial, of 14 healthy subjects trained as a satiety panel. At each of six two-hour satiety sessions, subjects consumed one of three different test meals on two separate occasions. The test meals were: a standard meal plus 5 g PGX; a standard meal plus 4.5 g of PGX as softgels; and a standard meal plus 5 g of WD. Subjects recorded fullness using a labelled magnitude scale at 0, 15, 30, 45, 60, 90, and 120 min and the total area under the curve (AUC), mean fullness vs. time was calculated. The meals with PGX (in granular and softgel form) gave higher satiety (AUC) (477 ± 121 and 454 ± 242 cm·min), than the meal with WD (215 ± 261 cm·min) (p < 0.001). Subjects had blood glucose levels measured after the meals with PGX (granules) and WD. Glucose response (AUC) was significantly lower (p < 0.001) after the PGX meal than for the WD meal.  The high viscosity reported for PGX is a likely mechanism behind the significant satiety and blood glucose modulating effects observed in this study.